Patient Perceptions of Care as Influenced by a Large Institutional Pharmacogenomic Implementation Program. Issue 1 (4th April 2017) - McKillip, RP; Borden, BA; Galecki, P; Ham, SA; Patrick‐Miller, L; Hall, JP; Hussain, S; Danahey, K; Siegler, M; Sorrentino, MJ; Sacro, Y; Davis, AM; et al.
Abstract : Despite growing clinical use of genomic information, patient perceptions of genomic‐based care are poorly understood. We prospectively studied patient‐physician pairs who participated in an institutional pharmacogenomic implementation program. Trust/privacy/empathy/medical decision‐making (MDM)/personalized care dimensions were assessed through patient surveys after clinic visits at which physicians had access to preemptive pharmacogenomic results (Likert scale, 1 = minimum/5 = maximum; mean [SD]). From 2012–2015, 1, 261 surveys were issued to 507 patients, with 792 (62.8%) returned. Privacy, empathy, MDM, and personalized care scores were significantly higher after visits when physicians considered pharmacogenomic results. Importantly, personalized care scores were significantly higher after physicians used pharmacogenomic information to guide medication changes (4.0 [1.4] vs. 3.0 [1.6]; P < 0.001) compared with prescribing visits without genomic guidance. Multivariable modeling controlling for clinical factors confirmed personalized care scores were more favorable after visits with genomic‐influenced prescribing (odds ratio [OR] = 3.26; 95% confidence interval [CI] = (1.31–8.14); P < 0.05). Physicians seem to individualize care when utilizing pharmacogenomic results and this decision‐making augmentation is perceived positively by patients.